2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition Workshops (CVPRW) 2019
DOI: 10.1109/cvprw.2019.00199
|View full text |Cite
|
Sign up to set email alerts
|

FeatherNets: Convolutional Neural Networks as Light as Feather for Face Anti-Spoofing

Abstract: Face Anti-spoofing gains increased attentions recently in both academic and industrial fields. With the emergence of various CNN based solutions, the multi-modal(RGB, depth and IR) methods based CNN showed better performance than single modal classifiers. However, there is a need for improving the performance and reducing the complexity. Therefore, an extreme light network architecture(FeatherNet A/B) is proposed with a streaming module which fixes the weakness of Global Average Pooling and uses less parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 32 publications
0
45
0
Order By: Relevance
“…In [48], patches with fixed-size are randomly extracted from cropped face areas, which can strength the ability of CNNs for perceiving spoof clues on the texture attribute other than the whole facial structure attribute. However, it is timeconsuming to traverse all patches for network inference.…”
Section: Multiscale Patch and Weighted Fine-tuningmentioning
confidence: 99%
“…In [48], patches with fixed-size are randomly extracted from cropped face areas, which can strength the ability of CNNs for perceiving spoof clues on the texture attribute other than the whole facial structure attribute. However, it is timeconsuming to traverse all patches for network inference.…”
Section: Multiscale Patch and Weighted Fine-tuningmentioning
confidence: 99%
“…Learning: Because of its popularity, deep learning techniques are also considered effective in solving the issue of building an anti-spoofing system. In the deep learning technique, a convolution neural network is used to detect spoofing attacks [9]. The process takes an input image, a process that consists of neurons that have a function of weight, bias, and activation, then classify it into certain categories.…”
Section: ) Deepmentioning
confidence: 99%
“…ResNets [32], DenseNets [33] and most light networks, like MobileNetV2 [34], ShuffleNetV2 [35]. For face tasks, however, researchers [36], [37] have observed that CNNs with GAP layer are less accurate than those without GAP. Further, FeatherNets [37] replace the GAP with specially designed Streaming Module, and achieve significant performance for face anti-spoofing.…”
Section: ) the Weakness Of Gap In Fldmentioning
confidence: 99%
“…For face tasks, however, researchers [36], [37] have observed that CNNs with GAP layer are less accurate than those without GAP. Further, FeatherNets [37] replace the GAP with specially designed Streaming Module, and achieve significant performance for face anti-spoofing. Inspired by these works, we carry out experiments to evaluate the weakness of GAP in FLD and get the same conclusion ( Table 8).…”
Section: ) the Weakness Of Gap In Fldmentioning
confidence: 99%